A nanozyme-linked immunosorbent assay for dual-modal colorimetric and ratiometric fluorescent detection of cardiac troponin I - Miao, Luyang; Jiao, Lei; Tang, Qiaorong; Li, He; Zhang, Lianhua; Wei, Qin (Sensors and actuators. B, Chemical, 2019)
•A new kind of robust nanozyme-linked immunosorbent assay has been developed.•The proposed nanozyme-linked immunosorbent assay can achieve ratiometric fluorescent and colorimetric dual-modal detection.•This presented method affords robust, reliable and sensitive immunoassay performance. To develop a robust method for the detection of disease biomarkers is always the pursued goal in the field of biomedical research. Multi-modal immunoassay strategy will bring tremendous potential for the purpose. In this study, a kind of robust nanozyme-linked immunosorbent assay has been presented, which can achieve ratiometric fluorescent and colorimetric dual-modal sensing performance. Here, o-phenylenediamine (OPD) as an organic substrate can be oxidized and converted into 2,3-diaminophenazine (oxOPD) by the robust nanozyme of nanoceria with peroxidase-like properties in the present of H2O2. An exogenous fluorescence signal source of graphitic carbon nitride quantum dots (g-C3N4 QDs) is introduced, and the corresponding fluorescence can be efficiently quenched by oxOPD owing to the hydrogen bonding and π-π stacking interactions, yielding a fluorescence spectral line with dual emission peaks while only irradiated by an excitation wavelength. Meanwhile, a visible color change was derived from the oxOPD formation, which can be recorded by colorimetric method. As a proof-of-study demonstration, the detection of human cardiac troponin I was done. This method affords robust, reliable and sensitive detection performance due to the combination of the merits of ratiometric fluorescent assay and colorimetric assay. It is no doubt that our proposed approach will bring remarkable inspirations for biomedical researchers.